Note-taking as a Determinant of the Effectiveness of PowerPoint as a Lecture Aid - Zellhoefer, Ashley S.; Chase, Jonathan C.; Murken, Nathaniel B. (My University, 2010)
PowerPoint is a much used but little researched multimedia lecture aid. Few studies have shown that students appreciate PowerPoint assisted lectures, but rarely have demonstrated learning benefits. The most compelling finding to date is that PowerPoint enhances learners? interest in the lecture; cognitive benefits have been less established. we conducted an experiment that examined the interactive effects of PowerPoint and note-taking on learners? immediate recall and transfer of learning from a lecture.
Color poster with text and charts.
Keywords: Note taking; Microsoft PowerPoint (Computer file)--Educational aspects; Media programs (Education)--Evaluation; Posters; Learning--Audio-visual aids; Computer-assisted instruction--Evaluation